Sistem Pendukung Keputusan Untuk Mengevaluasi Internal Program Studi - Padiku, Indhitya Rahman; Widodo, Achmad (JSINBIS (Jurnal Sistem Informasi Bisnis), 2015)
The development of major and study program cannot be separated by some internal factors weather directly influenced number of new registration students or indirectly. It needs a method to both know and to analyze internal evaluation variables in major or study program.Â Naive Bayes Clasifier (NBC) method is the simple form of Bayesian network that assume all features are independent each other. NBC shows us a great performance entirely in accuracy and error level classification. NBC is able to differentiate irrelevance attribute and also classified some attributes in prediction needs. This research hopefully can be useful for major internal evaluating and study program in order to increase the number of new registration students. The classification by influenced of variables to evaluate the condition of both major and study program for the new registration students.